Hydroxyapatite nano-barium-strontium-titaniumoxide composites - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2011)
The aim of this study is to produce and to investigate the mechanical and microstructural properties of composite materials made of hydroxyapatite, obtained from natural bovine bone and nano barium strontium titanium oxide (5 and 10 wt%). Compositions were mechanical alloyed and compacted to pellets. The samples were subjected to sintering at different temperatures between 1000 degrees C and 1300 degrees C. Compression strength, Vickers microhardness as well as density were measured. SEM and X-ray diffraction studies were also conducted. With increasing sintering temperature, microhardness, compression strength and density of composites increased. With increasing addition of nano barium strontium titanium oxide (BST) to bovine hydroxyapatite (BHA), microhardness values of composites decreased at all sintering temperatures, but compression strength and density values of composites showed different tendency. Compression strengths of BHA-composites at low sintering temperatures were nearly the same, but their compression strengths at high sintering temperatures decreased with increasing nano BST addition. The best mechanical properties were obtained at 1300 degrees C sintering temperature with BHA-5wt% nano BST. Microhardness and compression strengths values of these nano oxide composites are generally higher than that BHA-composites produced by traditional methods. Adding of nano-oxides to BHA could be a valuable method to produce rigid and high load carrying ability when compared with BHA-composites produced by conventional methods. Nano-HA and nano-oxides composites could be even better. Those nano-nano studies are still in progress.
Keywords: Hydroxyapatite; Composites; New Materials; Nano-dopants; REINFORCED HYDROXYAPATITE; MECHANICAL-PROPERTIES; NANOCOMPOSITE